The Shepherdess' Progress: From Favart to Boucher to Sèvres. (2nd April 2016) - Zarucchi, Jeanne Morgan
Summary: A pair of Sèvres porcelain figurines, The Flute Lesson and The Grape Eaters, are known to be based upon scenes from a theatrical pantomime written by Charles-Simon Favart (1710–1792). A shepherd and shepherdess from the play were illustrated by François Boucher (1703–1770), in paintings that in turn inspired porcelain figures designed around 1752. The porcelains have been regarded as strictly imitative, without crediting the sculptor with any originality. The author seeks to challenge that assumption, by revisiting the original shepherd and shepherdess from Favart's play and analyzing in detail how the painter Boucher and the unknown sculptor of Sèvres provided their own interpretations. It will further be argued that the characterization of the shepherdess evolves, from the play to the painting to the sculpture, from youthful innocence to a more overt erotic complaisance.